Impact of maternal pulmonary insufficiency on fetal growth in pregnancy. (2nd April 2020) - Brun, Stephanie; L'Ecuyer, Emilie; Dore, Annie; Mongeon, François-Pierre; Guedon, Aude-Christine; Leduc, Line
Abstract: Rationale: It is known that fetal growth is usually proportional to left-sided cardiac output (CO), which parallels the right-sided CO and that congenital right-sided lesions are usually associated with better perinatal outcomes than left-sided lesions. Objective: Our objective was to document whether newborns from mothers with severe residual pulmonary valve insufficiency (PI) after surgical tetralogy of Fallot (TOF) or pulmonary valve stenosis (PS) correction have lower birth weight (BW) than newborns from mothers with absent, mild, or moderate PI. Methods: This is a retrospective cohort study of women affected with repaired TOF and corrected PS with varied severity of residual PI. Exclusion criteria were: left ventricular dysfunction, left-sided valvular heart disease, other right-sided structural heart disease, chronic hypertension, substance addiction, and incomplete follow-up. Pregnancies were divided into three groups: absent or mild PI, moderate PI, and severe PI. A generalized linear model with normal dependent variable distribution was built and the parameter estimation made with Generalized Estimation Equations (GEE) to take into account repeated mother in data. Variables such as gestational age at birth, maternal age, smoking, and body mass index were tested with bivariate analyses to assess their effect on BW. Only gestational age remained in the adjusted model. Results: A total of 45 patients were included (33 TOF and 12 PS) and 97 pregnancies were reported: 22 miscarriages (22.7%) (15 TOF, 7 PS) and 75 successful pregnancies (57 TOF, 18 PS). The patients were divided into three groups: 1) absent or mild PI, 2) moderate PI, and 3) severe PI groups, which comprised, respectively, 29 (15 TOF, 4 PS), 20 (10 TOF, 1 PS), and 26 successful pregnancies (8 TOF, 7 PS). Using three levels of PI (absent or mild, moderate, and severe), the unadjusted model showed a significant effect of level of PI on BW ( p  = .0118), as well as the adjusted model ( p  = .0263) with gestational age as a covariate. The estimated mean newborn's BW was 3055.8 g in the severe PI group, 3151.0 g in the moderate PI group, and 3376.4 g in the absent or mild group when adjusted for gestational age. Hence, we estimated that the mean newborn's BW is 321 g lower in the severe PI group compared with absent or mild PI group ((CI: 572.3; −68.9), p  = .0087). Conclusions: Pregnancy is usually well tolerated in repaired TOF and corrected PS. Severe PI either from repaired TOF or PS is at higher risk of lower newborn's BW. Special attention must be paid to the severity of PI. Fetal growth surveillance in the third trimester is warranted.